Fire Regimen and Spread of Plants Naturalized in Central Chile - Castro-Morales, S (2011)
Setting fires is an old practice of land management in the Mediterranean region of central Chile. Fire in the region is currently of predominantly human origin and previously published material suggests that the scheduling of these activities is associated with the spread of naturalized exotic species. Research into the effects of fire on both native and exotic Mediterranean vegetation in central Chile has increased notably over recent years. The objective of our review is to highlight new knowledge in this area of research from the last 30 years and to contribute to systematization and an explicit conceptual model which takes into account the effect of a fire regimen on the spread of exotic plants and the mechanisms involved. We begin with analyses of the fire regimen which is currently observed in one Region of central Chile and a subsequent exploration of the literature to identify the attributes mainly of the germination of seeds which are sensitive to fire and which apply to the exotic species that are abundantly naturalized in central Chile. According to the studies consulted, diverse mechanisms have been described which involve the effect of fire on the spread of exotic plants in central Chile. Life-history traits, tolerance, facilitation, and positive feedback between exotic plants and fire frequency have been mechanisms reported in the literature. Finally, we propose a conceptual model which represents dispersal assisted by humans of exotic species and the spread of species naturalized by the effect of fire regimens, which helps explain the composition and structure of the matorral of central Chile in an early successional state. © Sociedad de Biología de Chile.
Keywords: central Chile; exotic plant; fire; germination; naturalized plant